2011
DOI: 10.1258/smj.2011.011284
|View full text |Cite
|
Sign up to set email alerts
|

Walk or run? is high-intensity exercise more effective than moderate-intensity exercise at reducing cardiovascular risk?

Abstract: The benefits of exercise in the prevention of cardiovascular disease are irrefutable. However, the optimum 'dose' of exercise in order to derive the maximum cardiovascular benefit is not certain. Current national and international guidelines advocate the benefits of moderate-intensity exercise. The relative benefits of vigorous versus moderate-intensity exercise have been studied in large epidemiological studies, addressing coronary heart disease and mortality, as well as smaller randomized clinical trials whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 48 publications
1
31
0
3
Order By: Relevance
“…Our results lend some support to previous reviews, which have concluded that MOPA provides protection against depression and cardiovascular risk, but that vigorous-intensity PA provides greater protection (21,(23)(24)(25). Our adjusted results suggest that at 500-1000 METIminIwk j1 level (meeting guidelines), there is an 18% reduction (OR = 0.82, 95% CI = 0.75-0.91) in risk of HT for MOPA but a 27% reduction (OR = 0.73, 95% CI = 0.62-0.86) in risk in those who reported MVPA compared with the risk in the inactive referent group.…”
Section: Discussionsupporting
confidence: 90%
“…Our results lend some support to previous reviews, which have concluded that MOPA provides protection against depression and cardiovascular risk, but that vigorous-intensity PA provides greater protection (21,(23)(24)(25). Our adjusted results suggest that at 500-1000 METIminIwk j1 level (meeting guidelines), there is an 18% reduction (OR = 0.82, 95% CI = 0.75-0.91) in risk of HT for MOPA but a 27% reduction (OR = 0.73, 95% CI = 0.62-0.86) in risk in those who reported MVPA compared with the risk in the inactive referent group.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, cardioprotective effects of exercise have been extensively described [6]. It was shown that isoproterenol caused hypertrophy, necrosis, apoptosis, fibrosis, and reduced capillary size in the left ventricle (LV) [7]; interestingly, all negative effects of sympathetic hyperactivity were prevented by exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it has been suggested that exercise intensity, not frequency or duration, is the most important variable for cardioprotection [40]. Thus further study using varying levels of exercise and longer follow up after isoproterenol may provide more mechanistic insights into the relationship between exercise intensity and ATP metabolism in the RBC in its role in cardiovascular protection.…”
Section: Discussionmentioning
confidence: 99%